The Development of E-Worksheet “Diversity of Ferns” Based on a Scientific Approach to Train Students' Critical Thinking Skills - Alifrilia, Tarisa; Wisanti, Wisanti (Berkala Ilmiah Pendidikan Biologi (BioEdu), 2024)
Critical thinking skills is a crucial competency for the 21st century and is essential for students. The scientific approach can be applied in the teaching and learning process to train students' critical thinking skills through electronic-based teaching materials. This research aims to create an e-worksheet on the diversity of ferns using a scientific approach to train critical thinking skills that are valid, practical, and effective. The research method is applying the 4D development model (Define, Design, Develop, and Disseminate). The e-worksheet product was tested on a limited basis with 20 students from class X-1 at MAN 2 Gresik. Research parameters in developing the E-worksheet include the validity based on expert assessments, the practicality based on its implementation, and the effectiveness based on the achievement of critical thinking skills and student responses. Research instruments include validation assessment instruments, implementation observation sheets, critical thinking assessments, and student response questionnaire. Data analysis was conducted descriptively and quantitatively. The analysis results indicate that the E-worksheet’s validity is 3.97 (very valid), its practicality is 97.29% (very good), and its effectiveness in terms of the achievement of critical thinking skills, indicators of interpretation, analysis, evaluation, and explanation respectively worth 85%, 85%, 100%, and 100% (very good), as well as positive responses from students worth 98.82% (very good). Thus, this E-worksheet is declared valid, practical, and effective, so it is suitable to be applied to train students' critical thinking skills.